1984
DOI: 10.1083/jcb.99.1.119s
|View full text |Cite
|
Sign up to set email alerts
|

Properties of the 120,000- and 95,000-dalton actin-binding proteins from Dictyostelium discoideum and their possible functions in assembling the cytoplasmic matrix.

Abstract: The cell cortex of Dictyostelium amebae contains an actin-rich cytoplasmic matrix. Changes in geometry of this matrix are believed to regulate protrusive activity and motility of the cell cortex . Two actin-binding proteins (120,000 and 95,000 daltons [120K and 950 are present in the cell cortex, and their properties, many of which are described here for the first time, suggest that they regulate growth and organization of cortical microfilaments . The 120K protein is a flexible dimer 35 nm in length with a na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
65
0

Year Published

1986
1986
2000
2000

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(72 citation statements)
references
References 37 publications
7
65
0
Order By: Relevance
“…a-actinin and ABP-120 are F-actin cross-linking proteins in D. discoideum (Condeelis and Vahey, 1982;Condeelis et al, 1984). In mutants that lack either of them (Schleicher et al, 1988;Brink et al, 1990), spore actin rods were found both in the nucleus and the cytoplasm in a similar manner to that of the wild type strain (data not shown).…”
Section: Reconstruction Of Actin Tubules From Spore Supernatantsupporting
confidence: 53%
“…a-actinin and ABP-120 are F-actin cross-linking proteins in D. discoideum (Condeelis and Vahey, 1982;Condeelis et al, 1984). In mutants that lack either of them (Schleicher et al, 1988;Brink et al, 1990), spore actin rods were found both in the nucleus and the cytoplasm in a similar manner to that of the wild type strain (data not shown).…”
Section: Reconstruction Of Actin Tubules From Spore Supernatantsupporting
confidence: 53%
“…ABP and ABP-120 cross-link actin filaments in vitro to form a rigid actin gel containing orthogonal networks similar to those observed in pseudopods in situ (Condeelis et al, 1984;Hartwig and Shevlin, 1986;Wolosewick and Condeelis, 1986;Ogihara et al, 1988). Both proteins have also been localized to filament networks found in pseudopods in situ by immunoelectron microscopy (Hartwig and Shevlin, 1986; al., 1988;Cox et al, 1995).…”
Section: Introductionmentioning
confidence: 94%
“…The protein in Dictyostelium that is most likely to fulfill this cross-linking function is ABP-120. ABP-120 is a dimer consisting of two identical subunits each with a molecular weight of 120,000 on SDS-PAGE (Condeelis et al, 1984), which are packed in an anti-parallel orientation (Brink et al, 1990). Based on structural similarities, ABP-120 has been proposed to be a member of the filamin family of actin binding proteins, which is composed of ABP, ABP-280, and nonmuscle filamin (Hartwig and Kwiatkowski, 1991;Matsudaira, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…ABP-120 is incorporated into the actin cytoskeleton at times after stimulation with cAMP that correlate with cross-linking of actin into the cytoskeleton and pseudopod extension Dharmawardhane et al, 1989). ABP-120 crosslinks actin filaments in vitro to form a rigid actin gel containing orthogonal networks similar to those observed in pseudopods in situ (Condeelis et al, 1984, Wolosewick andCondeelis, 1986;Ogihara et al, 1988).ABP-120 is a 40-nm rod-shaped protein consisting of two identical subunits each with a molecular mass of 120,000 D on SDS-PAGE (Condeelis et al, 1984) or 92,200 D as inferred from sequence analysis (Noegel et at., 1989). Each monomer contains an amino-terminal actin filament-binding site which is highly conserved throughout a number of actinbinding protein families (Bresnick et al, , 1991.…”
mentioning
confidence: 99%
“…ABP-120 is a 40-nm rod-shaped protein consisting of two identical subunits each with a molecular mass of 120,000 D on SDS-PAGE (Condeelis et al, 1984) or 92,200 D as inferred from sequence analysis (Noegel et at., 1989). Each monomer contains an amino-terminal actin filament-binding site which is highly conserved throughout a number of actinbinding protein families (Bresnick et al, , 1991.…”
mentioning
confidence: 99%